Lusocom: a study of communications policies and discourses in the lusophone space - Sousa, Helena (2004)
Comunicação apresentada à International Communication Section da Conferência Científica da International Association for Media Communication Research (IAMCR) Scientific Conference, Porto Alegre, 2004.